Opresion/emancipacion de la enfermería. marcos evolutivos, manifestaciones y perspectivas - Sánchez Arce, Lydia Edita (2009)
Qualitative Investigation descriptive, with boarding dialectic and historical perspective. It characterized to study the process of the oppression/ emancipation of nursing Liberteña period 1980-2007. The theoretical referents are GRAMSCI (oppression and Hegemony), SCOTT (Gender) and DEMO (Political). 07 nurses participated in the teaching, assistance and entities associative. The delimitation was made with the technique of saturation, used the oral interview technique thematic and semantic analysis. As product of the compilation and analysis of the testimonies of los/as actor / ace, 3 thematic areas and his categories were identified: thematic Area evolutionary Frames of the process oppression / emancipation of the Infirmary(Nursing), categories: historical Events and sociopolitical and The events of kind(genre) 1980-2006 that influenced to oppress / emancipate to the infirmary(nursing). Thematic area Manifestations that favor and prevent the emancipation of the infirmary(nursing) liberteña, categories: professional Exercise(Fiscal year) with predominance intrahospitalario Vs. Professional exercise(fiscal year) with community predominance; Nurses formed(trained) with educational Biomedical model Vs. Nurses formed(trained) in educational perspective dialectical social; Nurses without political power Vs. Nurses with political power and labour oppressive System Vs. Labour system fairly social. Thematic area Perspectives to reach the emancipation of the Peruvian infirmary(nursing) and Liberteña, categories: To know and increasing Power, Strengthening of the social and professional identity and. Legal and social legitimacy of the Infirmary(Nursing). The offer of the work understood: Formation of the conscience of emancipation, formation(training) of professional and social groups, preparation in sabers and involucramiento professional, social, political.